A Novel High-Content Screening-Based Method for Anti-Trypanosoma cruzi Drug Discovery Using Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes. (15th August 2021) - Portella, Diogo Crispim Nascimento; Rossi, Erik Aranha; Paredes, Bruno Diaz; Bastos, Tanira Matutino; Meira, Cássio Santana; Nonaka, Carolina Vasques Kymie; Silva, Daniela Nascimento; Improta-Caria, Alex; Moreira, Diogo Rodrigo Magalhaes; Leite, Ana Cristina Lima; de Oliveira Filho, Gevanio Bezerra; Filho, José Maria Barbosa; et al.
Abstract : Chagas disease is caused by Trypanosoma cruzi infection and remains a relevant cause of chronic heart failure in Latin America. The pharmacological arsenal for Chagas disease is limited, and the available anti- T. cruzi drugs are not effective when administered during the chronic phase. Cardiomyocytes derived from human-induced pluripotent stem cells (hiPSC-CMs) have the potential to accelerate the process of drug discovery for Chagas disease, through predictive preclinical assays in target human cells. Here, we aimed to establish a novel high-content screening- (HCS-) based method using hiPSC-CMs to simultaneously evaluate anti- T. cruzi activity and cardiotoxicity of chemical compounds. To provide proof-of-concept data, the reference drug benznidazole and three compounds with known anti- T. cruzi activity (a betulinic acid derivative named BA5 and two thiazolidinone compounds named GT5A and GT5B) were evaluated in the assay. hiPSC-CMs were infected with T. cruzi and incubated for 48 h with serial dilutions of the compounds for determination of EC50 and CC50 values. Automated multiparametric analyses were performed using an automated high-content imaging system. Sublethal toxicity measurements were evaluated through morphological measurements related to the integrity of the cytoskeleton by phalloidin staining, nuclear score by Hoechst 33342 staining, mitochondria score following MitoTracker staining, and quantification of NT-pro-BNP, a peptide released upon mechanical myocardial stress. The compounds showed EC50 values for anti- T. cruzi activity similar to those previously described for other cell types, and GT5B showed a pronounced trypanocidal activity in hiPSC-CMs. Sublethal changes in cytoskeletal and nucleus scores correlated with NT-pro-BNP levels in the culture supernatant. Mitochondrial score changes were associated with increased cytotoxicity. The assay was feasible and allowed rapid assessment of anti- T. cruzi action of the compounds, in addition to cardiotoxicity parameters. The utilization of hiPSC-CMs in the drug development workflow for Chagas disease may help in the identification of novel compounds.